1991
DOI: 10.1038/clpt.1991.157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of menstrual cycle and gender on alprazolam pharmacokinetics

Abstract: The effects of menstrual cycle phases and gender on alprazolam pharmacokinetics were evaluated in normal volunteers. Alprazolam (1 mg) was administered to seven women during the late follicular and luteal phases of the menstrual cycle and to eight men on one occasion. No difference in alprazolam pharmacokinetic parameters was observed during the menstrual cycle phases. Mean alprazolam clearance (+/- SD) was 0.0037 +/- 0.0009 ml/hr during the follicular phase and 0.0036 +/- 0.001 ml/hr during the luteal phase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 7 publications
2
26
1
Order By: Relevance
“…More importantly, this requirement would have greatly increased the likelihood that women would refuse to participate. Given that alprazolam metabolism has not been shown to vary across the menstrual cycle (Kirkwood et al 1991), andCiraulo et al (1996) reported that alprazolam plasma levels were similar in FHP and FHN females following a single dose of alprazolam, we did not feel that collecting plasma levels in the present study was justified. However, changes in both electrophysiological activity and DSST performance have been shown to be correlated with alprazolam plasma levels (Kaplan et al 1998).…”
Section: Discussionmentioning
confidence: 49%
“…More importantly, this requirement would have greatly increased the likelihood that women would refuse to participate. Given that alprazolam metabolism has not been shown to vary across the menstrual cycle (Kirkwood et al 1991), andCiraulo et al (1996) reported that alprazolam plasma levels were similar in FHP and FHN females following a single dose of alprazolam, we did not feel that collecting plasma levels in the present study was justified. However, changes in both electrophysiological activity and DSST performance have been shown to be correlated with alprazolam plasma levels (Kaplan et al 1998).…”
Section: Discussionmentioning
confidence: 49%
“…Ciraulo et al (1988) found that pharmacokinetic variables for alprazolam in 17 abstinent male alcoholics (mean age 42 years) did not differ from 465 values observed in 12 healthy male controls of mean age 39 years. 5.10 Menstrual Cycle Kirkwood et al (1991) found no significant differences in pharmacokinetic parameters for alprazolam among 8 healthy women (mean age 26 years) when tested in the follicular and luteal phases of the menstrual cycle.…”
Section: Renal Diseasementioning
confidence: 89%
“…In 2 of the studies (Greenblatt et al 1983a;Kirkwood et al 1991) gender had no significant effect on alprazolam t'l>, Vd (in L/kg) or CL (in ml/min/kg). However, Kristjansson and Thorsteinsson (1991) observed significantly higher values of CL in young women as opposed to young men.…”
Section: Gendermentioning
confidence: 95%
“…These investigators used the metabolism of midazolam to 1'-hydroxymidazolam as an indicator of cytochrome P4503A activity. Owing to overlapping substrate specificities, confusion exists as to which specific isozymes of the CYP3A subfamily may undertake this reaction, as is the case for Alfentanil no difference clearance [79] Alprazolam no difference clearance [80,81] Dextromethophan no difference clearance (N-demethylation) [75,82] Eletriptan no difference clearance [83] Ethylmorphine no difference N-demethylation [84] Midazolam no difference clearance [85,86] Midazolam increase follicular 1-hydroxylation [87] Omeprazole no difference sulphone formation [88] CYP3A4 b…”
Section: Cytochrome P450 Mediated Biotransforma-tionmentioning
confidence: 99%